2004
DOI: 10.1200/jco.2004.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Breast Conservation After Neoadjuvant Chemotherapy: The M.D. Anderson Cancer Center Experience

Abstract: Breast conservation therapy after neoadjuvant chemotherapy results in acceptably low rates of LRR and IBTR in appropriately selected patients, even those with T3 or T4 disease. Advanced nodal involvement at diagnosis, residual tumor larger than 2 cm, multifocal residual disease, and lymphovascular space invasion predict higher rates of LRR and IBTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
233
7
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(261 citation statements)
references
References 47 publications
10
233
7
11
Order By: Relevance
“…Of the 268 patients treated with breast conserving surgery, 18 (7%) had radial margins involved by invasive carcinoma and 11 (4%) were recorded as having close surgical margins. These numbers compare favourably with another single institution series of 340 patients treated with neoadjuvant chemotherapy followed by breast conserving surgery (Chen et al, 2004). There have been a number of proposed methods for assessing pathological response to neoadjuvant chemotherapy in the treatment of early and locally advanced breast cancer.…”
Section: Discussionmentioning
confidence: 83%
“…Of the 268 patients treated with breast conserving surgery, 18 (7%) had radial margins involved by invasive carcinoma and 11 (4%) were recorded as having close surgical margins. These numbers compare favourably with another single institution series of 340 patients treated with neoadjuvant chemotherapy followed by breast conserving surgery (Chen et al, 2004). There have been a number of proposed methods for assessing pathological response to neoadjuvant chemotherapy in the treatment of early and locally advanced breast cancer.…”
Section: Discussionmentioning
confidence: 83%
“…In the same center, an index was developed on a scale of 0-4 which identified subgroups of patients with significantly different rates of LRR after chemotherapy followed by BCT [19,20]. Patients with a score of 4 had a higher chance of LRR than patients with a lower score.…”
Section: Discussionmentioning
confidence: 99%
“…For some authors, the diversity of pathologic findings indicates the need for mastectomy [16,17]. Other authors argue that the low recurrence rates reported in selected cases of T3 and T4 show that these patients could rather undergo conserving surgery [3,18]. This study indicates that oncoplastic surgical techniques are a useful approach to achieve this aim of getting adequate margins as well as achieving a cosmetically acceptable breast conservation.…”
Section: Discussionmentioning
confidence: 87%
“…The possibility of breast conservation in cases of LABC has been demonstrated in single-institution experiences with small numbers and long follow-up. There are also single institutional experiences with large number of LABC patients, but with short follow-up results [2][3][4]. The only prospective randomized trial, LAMANOMA, failed due to insufficient accrual of the patients [5].…”
Section: Introductionmentioning
confidence: 99%